Methadone treatment, bruxism, and temporomandibular disorders among male prisoners. (4th April 2016) - Enguelberg‐Gabbay, Judith V.; Schapir, Lior; Israeli, Yair; Hermesh, Haggai; Weizman, Abraham; Winocur, Ephraim
Abstract : There is little information on bruxism related to illicit drug use. Prolonged drug use may damage the stomatognathic system via oral motor overactivity. The aim of the present study was to compare the rates of bruxism and temporomandibular disorders (TMDs) between prisoners with and without drug‐use disorders, to evaluate the association between methadone treatment and bruxism and to assess the possible relationship between bruxism and pain. The sample included 152 male prisoners, 69 of whom were drug users maintained on methadone. All prisoners were examined by an experienced dentist and completed a questionnaire on their oral habits, with the aim of detecting signs or symptoms of TMD and/or bruxism. Additional data were collected from medical files. The prevalence of sleep bruxism and awake bruxism, but not of TMDs, was significantly higher among drug‐user than non‐drug user prisoners (52.2% vs. 34.9% for sleep bruxism, 59.7% vs. 30.1% for awake bruxism, and 46.3% vs. 25.6% for TMDs, respectively). Participants with awake bruxism were statistically more sensitive to muscle palpation compared with participants with sleep bruxism [rating scores (mean ± SD): 0.32 ± 0.21 vs. 0.19 ± 0.28, respectively]. An association was found between sleep bruxism and awake bruxism. It seems that there is a direct or an indirect association between methadone maintenance treatment and sleep bruxism or awake bruxism in male prisoners.